Dynamical analysis and soliton solutions of a variety of quantum nonlinear Zakharov–Kuznetsov models via three analytical techniques - Zaagan, Abdullah A.; Altalbe, Ali; Bekir, Ahmet (Frontiers in Physics, 2024)
Some new types of truncated M-fractional exact soliton solutions of the two important quantum plasma physics models; extended quantum Zakharov-Kuznetsov and extended quantum nonlinear Zakharov-Kuznetsov are successfully achieved by applying the exp a function technique, improved (G ′ /G)-expansion technique and Sardar sub-equation technique. These two models have many useful uses to explain the waves in the quantum electron-positron-ion magnetoplasmas as well as weakly non-linear ion-acoustic waves in plasma. The obtained results are in the form of dark, bright, periodic and other soliton solutions. The results are verified as well as represented by two-dimensional, three-dimensional and contour graphs. The results are newer than the existing results in the literature due to the use of fractional derivatives. Hence, the solutions are fruitful in future studies for these models. The obtained solutions are useful in the areas of Applied Physics, Applied Mathematics, Dynamical Systems, Nonlinear waves in Plasmas, and in dense space plasma. At the end, the applied techniques are simple, fruitful and reliable for solving the other models in mathematical physics.